2017
DOI: 10.4049/jimmunol.1600760
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Fever with Aphthous Stomatitis, Pharyngitis, and Cervical Adenitis Syndrome Is Associated with a CARD8 Variant Unable To Bind the NLRP3 Inflammasome

Abstract: Periodic fever with aphthous stomatitis, pharyngitis, and cervical adenitis (PFAPA) is a relatively common autoinflammatory condition that primarily affects children. Although tendencies were reported for this syndrome, genetic variations influencing risk and disease progression are poorly understood. In this study, we performed next-generation sequencing for 82 unrelated PFAPA patients and identified a frameshift variant in the gene (CARD8-FS). Subsequently, we compared the frequency of CARD8-FS carriers in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…Studies of the proband's mother and maternal aunt also revealed high circulating levels of IL-1β and increased NLRP3 inflammasome activity, but in these cases, possible clinical responses to anti-IL-1β administration have not been tested. These data on the relation of a CARD8 mutation to causation of CD is parallel to a recent finding that a frameshift mutation in CARD8, also leading to reduced binding of CARD8 with NLRP3, is a cause of periodic fever with aphthous stomatitis, pharyngitis, and cervical adenitis (6).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Studies of the proband's mother and maternal aunt also revealed high circulating levels of IL-1β and increased NLRP3 inflammasome activity, but in these cases, possible clinical responses to anti-IL-1β administration have not been tested. These data on the relation of a CARD8 mutation to causation of CD is parallel to a recent finding that a frameshift mutation in CARD8, also leading to reduced binding of CARD8 with NLRP3, is a cause of periodic fever with aphthous stomatitis, pharyngitis, and cervical adenitis (6).…”
Section: Discussionsupporting
confidence: 72%
“…Whole exome sequencing identified a number of variants in the patients who composed the above kindred (Supplemental Figure 1). Among these, the variant chr19:48741719 C>T (hg19) in CARD8 stood out because of its role in the inflammasome (5,6). This variant has an allele frequency of 0.0015% in the genome Aggregation Database (gnomAD; http://gnomad.broadinstitute.org/) (2 heterozygous individuals), is predicted to be possibly damaging/ deleterious by PolyPhen (http://genetics.bwh.harvard.edu/pph/ data/) and SIFT (http://sift.jcvi.org/), and has a CADD-PHRED score (http://cadd.gs.washington.edu/info) of 11.3, which is above In initial studies to examine this latter possibility, we determined concentrations of IL-1β and IL-6 in a random sample of proband serum by ELISA and found that concentrations of both of these cytokines were clearly increased compared with levels in sex-matched control sera ( Figure 2B).…”
Section: Clinical Courses Of Patients In a Kindred With A Card8 Mutatmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported an association between PFAPA symptoms and proinflammatory cytokine IL-1β production (4, 5). Cheung et al reported that a CARD8 polymorphism (CARD8-FS) in inflammasome-related genes was more common in PFAPA patients with a more severe phenotype (21). A TE, with removal of the microbial layer on the tonsils, in addition to lymphatic tissue, is a highly effective treatment for PFAPA syndrome (22).…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52][53] In an additional report, an association between PFAPA and a CARD8 variant that is unable to bind the NLRP3 inflammasome was found. 54 Decreased ability of CARD8 to bind NLRP3 is consistent with increased inflammasome activity and IL-1b production. Developing a better understanding of this overlay may further elucidate the precise mechanism through which the inflammasome influences PFAPA flares, ultimately leading to targeted therapeutic strategies.…”
Section: Il-1 In the Pathogenesis Of Pfapamentioning
confidence: 90%